How mycorrhiza symbiosis help coriander (Coriandrum sativum L.) plants grow better under contaminated soil?. (8th August 2020) - Fatemi, Hamideh; Esmaielpour, Behrooz; Sefidkon, Fatemeh; Soltani, Ali-Ashraf; Nematollahzadeh, Ali
Abstract: Heavy metals (HMs) are environmental pollutants of great concern to plants because of their high potential toxicity, and plants that are not able to tolerate high concentrations of HMs in the soil can become tolerant or increase their performance when associated with arbuscular mycorrhizal (AFM) fungi. A greenhouse pot experiment was conducted to study the impact of arbuscular mycorrhiza on traits of Coriander plants under Pb stress. Experimental factors included soil contamination with Pb (0, 500, 1000, and 1500 ppm) and mycorrhizal fungus inoculation ( Glomus mosseae ). Biomass, photosynthetic pigments, enzymatic and non-enzymatic antioxidants, Malondialdehyde (MDA) content, Pb concentration in shoot and root, and root colonization were recorded. Pb stress affected coriander traits such as decreased biomass, photosynthetic pigments such as chlorophyll a, chlorophyll b, total chlorophyll, and carotenoid almost 57, 13, 50, 23 and 10%, respectively. Also in contrast phenol, flavonoid in non-inoculated treatments, activities of superoxide dismutase (SOD), and peroxidase (POD) enzymes, and accumulation of malondialdehyde accumulation increased with increasing Pb concentrations, but catalase (CAT) activity increased just until 500 ppm Pb. Symbiosis with mycorrhizal fungi decreased the toxic effects of Pb stress on coriander plants via some mechanism such as adjusting enzymatic and non-enzymatic antioxidants and protecting photosynthetic pigments. The Pb accumulation decreased almost 9 and 15% in root and shoot by 1500 ppm Pb, respectively In general, these results suggest that mycorrhizal inoculation inhibits the detrimental effects of Pb stress on coriander plants.